Liars! Cheaters! Evildoers! : Demonization and the End of Civil Debate in American Politics. - DeLuca, Tom, 1946- (NYU Press, 2005)
The level of vitriol in American politics has been rising with no end in sight. Terms like "evildoer," "war on terror," and "axis of evil" have become commonplace in our discussion of international politics. What ever happened to civil debate? Where has all this moralizing come from? And what harm has this new level of attack caused to democracy in America?. In this compelling and cogent account, Tom De Luca and John Buell chart the rise of what they rightly label as the "demonization"of American politics, showing how political campaigns often neglect debates over policy in favor of fights ove.